Estudio de la Afectación en la Obtención de Crédito en la Cooperativa de Ahorro y Crédito 13 de Abril Matriz Ventanas - Chaulan Contreras, Karen Gisell (2017)
Ecuador has an approximate 887 savings and credit cooperatives, so it is located in the second country with the largest number, the first cooperatives arose mainly in Guayaquil, then expanded throughout the country, these institutions are very important for the financing and development of the world as they not only help the poorest sectors but are also an engine of the economy. Hence the importance of its regulation, as of January 2013 the Savings and Credit Cooperatives Subsystem was controlled by the Superintendency of Popular and Solidarity Economy, which promotes compliance with prudential regulations and regulations, requiring its actions to be adjusted and internal processes to the new regulatory framework.